Choice of Rational Antibiotic Therapy in Children with Bacterial Respiratory Diseases Under Increased Antibiotic Resistance Level - G.O. Lezhenko; O.Ye. Pashkova; L.I. Pantyushenko (Zaslavsky O.Yu., 2014)
The paper addresses the problems of the etiology of bacterial respiratory diseases in children, as well as antibiotic resistance of clinical strains of this pathology. It is found that in 52.7 % of cases, the causative agent of bacterial respiratory diseases in children was Haemophilus bacteria genus. The performed analysis of antibiogram showed that at the present stage starting antibacterial drug for empirical treatment of bacterial respiratory tract infections in children are the third generation cephalosporins.